Specific Heat on Single-crystalline YVO3 - Agustinus Agung Nugroho; Thomas T. M. Palstra (Journal of Magnetism and Its Applications, 2021)
The specific heat of single-crystalline YVO3 was measured from 2 K up to 250 K at zero field. The results reveal three transitions, at around 75, 115, and 200 K. The transitions at around 115 K and 200 K show that the phase transition is of the second-order type, whereas at around 75 K, unusual features of the specific heat are found. These unusual features are attributed to the effect of a large change in the volume. The specific heat data were analyzed in terms of a lattice contribution, a Schottky contribution and an excess magnetic contribution at high temperature. The magnetic contribution well above the magnetic ordering temperature is ascribed to short-range interactions due to the presence of strong magnetocrystalline anisotropy. The magnetic entropy considered by using this approach is 9.13 J/mole K which is close to the theoretical estimate for the S = 1 system.